Development of The Shot Put Exercise Model - Ucok Hasian Refiater; Nurhayati Liputo; Arief Ibnu Haryanto (Halaman Olahraga Nusantara : Jurnal Ilmu Keolahragaan, 2022)
The purpose of this development research is to produce the latest model of shot put practice, with the result of a book product developing the latest shot put training model that can be used in shot put practice. The method used in this research is development research adopted by the ADDIE model development research design. The place where the research was carried out on the Universitas Negeri Jakarta KOP shot put athletes was 23 people at the Rawamangun Athletic Stadium, East Jakarta. Data was collected by observation, interviews and questionnaires. The stages of data collection are carried out in the early stages, which consist of five stages starting from Analysis, Design, Development, Implementation and Evaluating, testing effectiveness and normality using statistical methods. The results of the study prove that from the evaluation results of athletic experts, shot putters and motion experts, it was found that overall this product met the criteria of being eligible so that it could be used in the next stage of research. The conclusion is seen and proven that the development of this shot put training model is effective in increasing the repulsion results of shot put athletes.